SDS-degrading Bacterium Isolated from a Paddy Field (Asian Journal of Plant Biology, 2022)
A bacterium capable of degrading sodium dodecyl sulphate (SDS) isolated from a paddy field water is characterized. In this report, we showed that almost complete degradation of SDS was observed in 6 to 10 days when the bacterium was grown on medium supplemented with SDS ranging from 0.75 to 1.75 g/L while higher concentrations showed partial degradation with no degradation was observed at concentrations higher than 2.0 g/L. The SDS-degrading bacterium was partially identified and provisionally named Pseudomonas sp. strain Maninjau1. We also showed that the presence of metal ions such as silver, copper, cadmium, chromium, lead and mercury inhibit the ability of the bacterium to degrade SDS by 50%. Growth kinetic studies show a correlation coefficient value of 0.99 for the Haldane model indicates it fits the curve while a low correlation coefficient value of 0.67 for the Monod model indicates poor fitting. The specific growth rate μ was discovered to rise as the substrate concentration was increased but it reached a peak value followed by a slow decrease indicating substrate inhibition. The calculated qmax or maximum degradation rate was 0.917 h-1 (95% confidence interval or C.I. from 0.664 to 1.171) while the saturation constant Ks or half velocity constant was 0.178 g/L SDS (95% C.I. from 0.089 to 0.266). The inhibition constant Ki was 0.605 g/L SDS (95% C.I. from  0.358 to 0.941). The very high maximum degradation rate obtained in this study indicates that this bacterium can be an efficient agent for bioremediation of SDS especially in soils.
Keywords: Sodium Dodecyl Sulphate; SDS-degrading bacterium; Pseudomonas sp.; paddy field; Inhibition kinetics